2017
DOI: 10.5578/ced.201706
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalance of Hepatitis B, Hepatitis C and Hepatitis D in Children Between 0-18 Years of Age Attenting to Our Hospital

Abstract: Objective: Detection of seroprevalence and possible transmission routes of hepatitis B virus (HBV), hepatitis C virus (HCV) and hepatitis D virus (HDV) in children between the ages of 0 and 18 accepted our hospital due to any complaints. Material and Methods: From blood taken from 208 patients that accepted to our hospital children's policlinics due to any complaint, serology of Hepatitis B, Hepatitis C (HBsAg, anti-HBs, anti-HBC IgG, anti-HBC IgM, anti-HCV) via chemiluminescent microparticle immunoassay (CMIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the study by Kılıçaslan et al, with 192 patients aged 10-19 years old, anti-HBs positivity rate was 61.9% (23). In another study by Duran et al, with 208 patients, this rate was 68.3% (9). Similarly, in the study of Sarıgül et al, with 1546 pediatric patients, anti-HBs positivity was 69.9% (10).…”
Section: Resultsmentioning
confidence: 86%
“…In the study by Kılıçaslan et al, with 192 patients aged 10-19 years old, anti-HBs positivity rate was 61.9% (23). In another study by Duran et al, with 208 patients, this rate was 68.3% (9). Similarly, in the study of Sarıgül et al, with 1546 pediatric patients, anti-HBs positivity was 69.9% (10).…”
Section: Resultsmentioning
confidence: 86%
“…During the study period of 35 years, 111 publications were found 13–123 . Among inactive HBV carriers, 34 studies reported HDV prevalence and it did not change significantly over three decades 6,13–45 (Table 1).…”
Section: Resultsmentioning
confidence: 99%